2009
DOI: 10.2967/jnumed.108.055152
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Resolution and Sensitivity of the Inveon Small-Animal PET Scanner

Abstract: The Inveon small-animal PET scanner is characterized by a large, 127-mm axial length and a 161-mm crystal ring diameter. The associated high sensitivity is obtained by using all lines of response (LORs) up to the maximum ring difference (MRD) of 79, for which the most oblique LORs form acceptance angles of 38.3°with transaxial planes. The result is 2 phenomena that are normally not encountered in PET scanners: a parallax or depth-of-interaction effect in the axial direction and the breakdown of Fourier rebinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(176 citation statements)
references
References 11 publications
7
168
1
Order By: Relevance
“…Visser et al reported that the deterioration in axial resolution associated with conventional FORE for 2-D reconstruction could be improved by using 3-D reconstruction without the rebinning step. However, FORE and 2D reconstruction are still widely used because of the greater complexity and longer reconstruction time required for 3D algorithms (23). Similar results were reported by Baghaei et al in 2004 (24).…”
Section: Discussionsupporting
confidence: 76%
“…Visser et al reported that the deterioration in axial resolution associated with conventional FORE for 2-D reconstruction could be improved by using 3-D reconstruction without the rebinning step. However, FORE and 2D reconstruction are still widely used because of the greater complexity and longer reconstruction time required for 3D algorithms (23). Similar results were reported by Baghaei et al in 2004 (24).…”
Section: Discussionsupporting
confidence: 76%
“…Simultaneous events can be identified and are presumed to be the two opposing gamma rays, revealing a "line of response" between the two detector positions. A modern small animal scanner can give image resolution measured as 1.5-1.8 mm (84,85). New clinical systems can achieve spatial resolution of approximately 4 mm (86), giving richer anatomical detail in humans (diameter approximately 400 mm or 100 times the resolution) than is currently available in mice (diameter approximately 30 mm or 20 times the resolution).…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The PET component consists of 1.5 · 1.5 · 10 mm lutetium oxyorthosilicate crystal elements with a ring diameter of 16.1 cm, providing a 10-cm transaxial and a 12.7-cm axial field of view (27)(28)(29).…”
Section: F-fdg Petmentioning
confidence: 99%